Acitretin in erosive penile lichen planus. (30th June 2016) - Poon, Flora; De Cruz, Ryan; Hall, Anthony
Abstract: Lichen planus (LP) is an incompletely understood T‐cell mediated auto‐immune dermatosis. When LP involves the genitalia it may present as painful, pruritic erosions that can be exquisitely tender, causing distress and genitourinary and sexual dysfunction. Management of erosive genital LP is often suboptimal. Despite higher order evidence demonstrating the efficacy of oral acitretin in the management of cutaneous and oral LP, it still features below other immunosuppressive and immunomodulatory therapies in many clinicians' therapeutic ladder. We present a case of severe erosive penile LP, successfully treated with oral acitretin after topical and oral corticosteroids failed to induce remission.